Pin-retained vs. dentinal slot retained amalgam onlay - Yao, Jerry C.S.; Ramos, Edward C.
Self-threading pins and dentinal slots were each placed in the area of sound dentin in twenty premolar specimens. Each specimen was filled with an amalgam onlay filling. The specimens were subjected to a tensile load until the breaking point of the amalgam onlay filling. The tensile load for each specimen was computed in pounds per square inch (PSI). The results show that the self-threading pins give better retention to the filling than the dentinal slot. However, the self-threading pin decreased the strength of the amalgam onlay filling.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental amalgams; Fillings (Dentistry).